Prognostic value of plasma N‐terminal pro B‐type natriuretic peptide levels in pneumonia patients requiring intensive care unit admission. Issue 6 (25th July 2013) - Lin, Shih‐Chang; Tsai, Yi‐Ju; Huang, Chun‐Ta; Kuo, Yao‐Wen; Ruan, Sheng‐Yuan; Chuang, Yu‐Chung; Yu, Chong‐Jen
Abstract: Background and objective: : Correct and early risk stratification for critically ill pneumonia patients remains an unmet medical need. This study aimed to test whether N‐terminal pro B‐type natriuretic peptide (NT‐proBNP) can serve as a prognostic marker in this setting. Methods: This prospective study enrolled 216 pneumonia patients admitted to intensive care unit. Plasma NT‐proBNP samples were obtained upon admission and primary outcome was all‐cause mortality at 30 days. Meanwhile, Acute Physiology and Chronic Health Evaluation (APACHE) II and Infectious Diseases Society of America/American Thoracic Society (IDSA/ATS) 2007 minor criteria were assessed. Results: Overall 30‐day mortality was 30%. NT‐proBNP levels were significantly higher in nonsurvivors than survivors (11 938 ± 13 121 vs 5658 ± 9240 pg/mL, P  = 0.001). Area under receiver operating characteristic curves of NT‐proBNP, APACHE II and IDSA/ATS 2007 minor criteria were not significantly different regarding prediction of mortality (0.715, 0.754 vs 0.654, P  = 0.085). Adding NT‐proBNP to APACHE II significantly increased the area under receiver operating characteristic curve from 0.754 to 0.794 ( P  = 0.048). Receiver operating characteristic analysis revealed optimal NT‐proBNP and APACHE II cut‐offs of 2177.5 pg/mL and 25.5, respectively. In multivariate analysis, both NT‐proBNP and APACHE II values above cut‐offs had a significantly higher probability of death than those below cut‐offs. A categorical approach combining NT‐proBNP and APACHE II cut‐offs provides additional risk stratification over a single marker approach. Conclusions: For pneumonia patients admitted to intensive care unit, NT‐proBNP strongly and independently predicts mortality, and its prognostic accuracy is comparable with APACHE II and IDSA/ATS 2007 minor criteria. Abstract : In adult patients admitted to the ICU with pneumonia, NT‐proBNP levels independently predict mortality with a prognostic accuracy that is comparable with that of APACHE II scores and IDSA/ATS 2007 minor criteria. The findings extend the prognostic utility of NT‐proBNP for critically ill pneumonia patients. See Editorial, page 889